74+15:5-7×9+14:2 ; 9×(1+49:7:7)-12:6×(5-12:4)
=9*(1+7:7)-12:6*(5-3)=
=9*(1+1)-12:6*2=
=9*2-2*2=
=18-4=
=14
Răspunsuri la întrebare
Răspuns de
1
74+15:5-7*9+14:2=
=74+3-63+7=
=77-70=
=7
9*(1+49:7:7)-12:6*(5-12:4)=
=9*(1+7:7)-12:6*(5-3)=
=9*(1+1)-12:6*2=
=9*2-2*2=
=18-4=
=14
=74+3-63+7=
=77-70=
=7
9*(1+49:7:7)-12:6*(5-12:4)=
=9*(1+7:7)-12:6*(5-3)=
=9*(1+1)-12:6*2=
=9*2-2*2=
=18-4=
=14
Răspuns de
1
74+15/5-7x9+14/2
74+3-63+7
77-70
7
9x(1+49/7/7)-12/6x(5-12/4)
9x(1+7/7)-2x(5-3)
9x(1+1)-2x2
9x2-4
18-4
14
74+3-63+7
77-70
7
9x(1+49/7/7)-12/6x(5-12/4)
9x(1+7/7)-2x(5-3)
9x(1+1)-2x2
9x2-4
18-4
14
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
=74+3-63+7=
=77-70=
=7